HEREDITARY COAGULOPATHIES: PATHOGENESIS AND LABORATORY DIAGNOSTICS - Makhamova Mokhidil,; Umarova Tamila Abdufattoevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Introduction. Hereditary coagulopathies are a group of genetically determined disorders of the hemostatic system characterized by impaired blood coagulation and an increased tendency to bleeding. These conditions are associated with a deficiency or functional insufficiency of coagulation factors, proteins of the coagulation cascade, or components responsible for their activation. The most well-known forms of hereditary coagulopathies include hemophilia A and B, von Willebrand disease, and rare coagulation factor deficiencies. Early diagnosis of these disorders is of crucial importance for the prevention of severe hemorrhagic complications and for improving patients’ quality of life.